Notice of Removal: Multi-hop wireless ad-hoc network routing protocols- a comparative study of DSDV, TORA, DSR and AODV - Yadav M.; Gupta S.K.; Saket R.K. (My University, 2025)
Development of many new routing protocols has been done in few past years to deal with multi-hop nature of adhoc networks. The requirement of multi-hop environment for adhoc network is due to less coverage range of the mobile nodes in wireless networks, as multi-hops may be required to transfer data between two nodes. In this paper, we have done a lot of packet-level simulation to compare the four routing protocols namely: DSDV, TORA, DSR, and AODV. Results have been carried out by using ns-2 simulator and used mobility model is random waypoint model. We have compared the performance of routing protocols not only on a particular traffic load but under certain range of different parameters like offered traffic load and pause time. The offered traffic load is varied as 0, 10, 20, 30 or 40 CBR sources and pause time varies as 0, 100, and 200 and so on, up to 700 seconds. The two performance metrics: packet delivery ratio and routing overheads have been used for comparison between four routing protocols. © 2015 IEEE.